2011
DOI: 10.1007/s10751-011-0298-4
|View full text |Cite
|
Sign up to set email alerts
|

The LPCTrap experiment: measurement of the β-ν angular correlation in 6He+ decay using a transparent Paul trap

Abstract: The LPCTrap experiment is devoted to the precise measurement of the β-ν angular correlation parameter, a βν , in the pure Gamow-Teller decay of 6 He + . This experiment is motivated by the search of the presence of tensor type contributions in the weak interaction. The radioactive source is confined in a transparent Paul trap installed at LIRAT, the low energy beam line of the SPIRAL facility. The β-ν correlation is studied by measuring the time of flight of the recoil ions detected in coincidence with the β p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Analysis of a first measurement with 6 He [302,322], with a total of about 10 5 β-recoil coincidence events recorded yielded a = −0.3335(73) stat (75) syst , in agreement with the SM value a GT = −1/3. A subsequent measurement with more than an order of magnitude higher statistics is still being analyzed [182,323,324]. In the meantime measurements with 19 Ne and 35 Ar have been performed as well [182,321].…”
Section: β − ν Correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of a first measurement with 6 He [302,322], with a total of about 10 5 β-recoil coincidence events recorded yielded a = −0.3335(73) stat (75) syst , in agreement with the SM value a GT = −1/3. A subsequent measurement with more than an order of magnitude higher statistics is still being analyzed [182,323,324]. In the meantime measurements with 19 Ne and 35 Ar have been performed as well [182,321].…”
Section: β − ν Correlationmentioning
confidence: 99%
“…[263][264][265]270] Being commissioned O(0.001) [276] UCNA-Nab-Leuven (LANL) [271,272,276] Analysis ongoing ( 45 Ca) b n < 0.05 [293,294] UCNA (LANL) [390] Ongoing with A n data 0.03 [295] PERKEO III (ILL) [295] Possible with A n data 0.003 [289] Nab (LANL) [188,289,357,358] In preparation 0.001 [291] PERC (Munich) [291,292] Planned a F 0.1% [306] TRINAT (TRIUMF) [306,310] Planned ( 38 K) 0.1% [343] TAMUTRAP (TA&M) [343] Superallowed β p emitters 0.1% [79] WISArD (ISOLDE) [79,177] In preparation ( 32 Ar β p decay) a not stated Ne-MOT (SARAF) [311,312] In preparation ( 18 Ne, 19 Ne, 23 Ne) a GT O(0.1)% [315] 6 He-MOT (Seattle) [313,315] Ongoing ( 6 He) not stated EIBT (Weizmann Inst.) [316][317][318] In preparation ( 6 He) 0.5% [182] LPCTrap (GANIL) [182,321,323,324] Analysis ongoing ( 6 He,…”
Section: Coefficientmentioning
confidence: 99%
“…The response functions of the β telescope and of the MCPPSD were also included in the MC simulation. It has previously been shown [21] that the shape of the TOF spectrum strongly depends on the ion cloud temperature and on the ions flight distances. The whole simulation was therefore carried out assuming different cloud temperatures around kT = 0.1 eV, and for different positions of the MCPPSD relative to the trap.…”
Section: Figmentioning
confidence: 99%
“…Simulations have shown that this parameter could also be determined with higher precision, if considered as a free parameter of the fit of the RI ToF distribution [21]. Indeed the shape of the leading edge of this distribution depends strongly on the cloud temperature and not on the value of a  .…”
Section: The  Angular Correlation Parametersmentioning
confidence: 98%